Pubertal stage and overweight in school children from São José dos Campos, SP - Inácio Bezerra Leão Filho; Mathias Roberto Loch; Virginia Oliveira da Silva; Elizabeth Maria Bismarck-Nasr; Bruno Natale Pasquarelli (Universidade Federal de Santa Catarina, 2010)
The aim of this study was to analyze the anthropometric characteristics and overweightaccording to chronological age and sexual maturation of school children from São José dosCampos - SP. The sample consisted by 2.802 school children of 10 to 12 years old of both sexes,1.522 boys. Variables measured were: height, weight, waist circumference, triceps and subscapularskinfolds thickness and the body mass index (BMI). We used the cutoff points of Cole etal.(2000) to classify the subjects according to sex and age. To determine the maturation stagewas utilized the Tanner's protocol in relation to pubic hair in both girls and boys. No differenceswas verified in overweight in accordance with maturation state. In boys the prevalence ofoverweight increased after P3 (P1: 22,4%; P2: 23,7%; P3: 27,8%) and decreased to P4 (22,7%).In girls, overweight increased after P2 (P1: 18%; P2: 22,2%) and decreased in other stages (P3:21,7%; P4: 14,1%). In the present study, the results shown that sexual maturation process hasan influence on the prevalence of overweight different in boys and girls, there were reported thesame results in the literature.